Divergent evolutionary paces among eudicot plants revealed by simultaneously duplicated genes produced billions of years ago - Wang, Yao; Wang, Jiangli; Li, Yingjie; Jin, Yongchao; Wang, Xiyin (Frontiers in Plant Science, 2025)
Polyploidization often occurs more than once along an evolutionary lineage to form extant plants. Major core eudicot plants share a whole-genome triplication (ceWGT), through which thousands of simultaneously duplicated genes are retained in extant genomes, providing a valuable starting line to check the difference in their evolutionary paces. Here, by characterizing the synonymous nucleotide substitutions (Ks) between these duplicates from 28 representative plants from 21 families, we checked the various evolutionary rates among plants among plants subjected to different rounds of extra polyploidization events. We found up to 68.04% difference in evolutionary rates among the selected plants. A statistical correlation analysis (correlation coefficient =0.57, at significant level = 0.01) indicated that plants affected by extra polyploidies have evolved faster than plants without such extra polyploidies showing that (additional) polyploidization has resulted in elevated genetic diversity. Comparing the plants affected by additional polyploidization and plants without it, the duplicated genes produced by the ceWGT and retained in extant genomes have gathered 4.75% more nucleotide substitutions in the former plants. By identifying the fast- and slowly evolving genes, we showed that genes evolving at divergent rates were often related to different evolutionary paths. By performing correction to evolutionary rates using a genome-scale approach, we revised the estimated timing of key evolutionary events. The present effort exploited the simultaneously duplicated genes produced by the shared polyploidization and help deepen the understanding of the role of polyploidization, especially its long-term effect in plant evolution and biological innovation.